2014
DOI: 10.4028/www.scientific.net/amm.687-691.4367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Super-Hydrophobic Copper Surface Fabricated by HS-WEDM

Abstract: We present a method to fabricate superhydrophobic surfaces on copper substrate using reciprocating type high speed wire cut electrical discharge machining (HS-WEDM) and self-assembly technology. Herein, single factor experiment was used to investigate the influence of several major parameters of the wire electrical discharge machining processing, such as pulse width, pulse gap (pulse interval) and power tube, on the contact angle of resulting surface. Results show that a composite structure, composed of crater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…High-speed wire cut EDM has been used by many researchers to generate hydrophobic and superhydrophobic surfaces on various metals, such as aluminium and aluminium alloys, copper, and so on. [53][54][55] Investigations have also been done to understand the role of machining and processing parameters like pulse width, pulse gap/interval and power tube. Wan et al have found that these influence the contact angles on the resulting surfaces.…”
Section: Multistep Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…High-speed wire cut EDM has been used by many researchers to generate hydrophobic and superhydrophobic surfaces on various metals, such as aluminium and aluminium alloys, copper, and so on. [53][54][55] Investigations have also been done to understand the role of machining and processing parameters like pulse width, pulse gap/interval and power tube. Wan et al have found that these influence the contact angles on the resulting surfaces.…”
Section: Multistep Processesmentioning
confidence: 99%
“…Wan et al have found that these influence the contact angles on the resulting surfaces. 53, 56 Figure 21 shows an Al-alloy surface generated using WEDM by Bae et al which shows superhydrophobic properties.…”
Section: Theory Of Superhydrophobic Surfacesmentioning
confidence: 99%
“…The machining parameters of the process control the derived microroughness, which in turn controls the wetting behavior of the surface. On a copper surface produced with WEDM and chemical surface modification for the enhancement of hydrophobicity, the increase in the pulse width and peak current led to a gradual decrease in the contact angle (CA) of specimens, while no correlation was found with the change in the pulse interval [40]. The current increase during the sink EDM of copper surfaces was reported to increase the CA, while surface roughness values (Ra and Rz) were found to increase and then decrease at higher currents (12 A) [36].…”
Section: Introductionmentioning
confidence: 99%
“…At present, few studies are available on preparing multi-scale microporous and hydrophobic surfaces on a metal substrate through EDM. Researchers have found that a surface has good hydrophobic properties when its structural characteristics are composed of craters, bulges, micropores, and particles [13,14]. A new process of preparing hydrophobic surfaces with micropores through EDM is proposed in the present study on the basis of previous studies that have shown that the surface of Ni-Ti alloy machined through EDM is mostly composed of craters and bulges [15].…”
Section: Introductionmentioning
confidence: 99%